Factors that encourage undergraduate youth in Universiti Malaysia Kelantan Venture into business - Syarizal Abdul Rahim; Mohd Firdaus Mohd Nasir; Ho Mei Yee (2014)
Entrepreneurship has been considered as the vital benefit realized by the businessman in overall development of national economy. The purpose of this paper is to investigate the factors that encourage the Universiti Malaysia Kelantan (UMK) undergraduate youth venture into business. This paper further highlights how the entrepreneurial education, personal attribute and business assistant and support encourage the UMK undergraduate youth venture into business. The sample size of this study was conducted among 100 UMK undergraduate students from different courses and year of study. The questionnaire based survey was used for data collection. This study has concludes all variables included during this study play a vital role in encouraging the undergraduate youth venture into business. Therefore, on the basis of findings, this paper concludes that undergraduate youth are motivated towards being an entrepreneur and venture into business.